Effect of food matrix and fermentation on angiotensin-converting enzyme inhibitory activity and β-glucan release after in vitro digestion in oat-based products. (March 2023) - Akan, Ecem; Karakaya, Sibel; Eda Eker Özkacar, Merve; Kinik, Özer
Hıghlıghts: Fermented and non-fermented oat-based products were produced with different consistency. Oat slurry medium is quite suitable for the growth of L. plantarum and yogurt bacteria. Fermentation can be a valuable process to release moderately high ACE inhibitory peptides originating from oat proteins. Fermentation did not significantly affect the amount of β-glucan in oat-based products. Graphical abstract: Abstract: The aim of this study was to determine the effects of fermentation and food matrix on the ACE inhibitory activities of the peptides obtained after in vitro gastrointestinal digestion, protein profiles (SDS-PAGE) and β-glucan amounts of oat products. Furthermore, the physicochemical and microbiological properties of fermented oat drinks and oat yogurt-like product obtained from oat fermentation were evaluated. Oat grains were mixed with a certain ratio of water 1:3 w/v (oat:water, yogurt consistency) and 1:5 w/v (oat:water, drink consistency), and this mixture was fermented with yogurt culture and probiotic Lactobacillus plantarum and fermented drinks and yogurt were produced. The results indicated that the fermented oat drink and the oat yogurt-like product had L. plantarum viability over 10 7 cfu/g. After the in vitro gastrointestinal digestion of the samples, the hydrolysis levels ranged from 57.70 % to 82.06 %. The hydrolysis level of the samples with fermented-drink consistency was significantly higher than the samples with yogurt consistency (p < 0.05). The SDS-PAGE profiles of the non-digested samples showed that the bands had molecular weights of 12–15 kDa and around 35 kDa. Bands whose molecular weights were around 35 kDA disappeared after gastric digestion. ACE inhibitory activities of the fractions composed of molecular weights of 2 kDa and 2–5 kDa obtained after in vitro gastrointestinal digestion of the oat samples were in the range of 46.93–65.91 %. The effect of fermentation on the ACE inhibitory activities of the peptide mixture with molecular weights between 2 and 5 kDa was not statistically significant, however, fermentation caused an increase in the ACE inhibitory activities of the peptide mixture with a molecular weight<2 kDa (p < 0.05). The β-glucan amounts of fermented and non-fermented oat products were in the range of 0.57–1.28 %. The β-glucan amounts detected after gastric digestion decreased considerably and β-glucan could not be detected in the supernatant after gastrointestinal digestion. This indicated that β-glucan did not solubilize in the supernatant (bioaccessible) and remained in the pellet. In conclusion, fermentation is a valuable process for releasing peptides with moderately high ACE inhibitory effects from the parent oat proteins.